Utilization of waste of old melinjo leaves for making quail egg pindang - Kusumorini, astuti (Pengabdian Cendekia, 2024)
Community education activity have been carried out in RT 8 RW 06 Jatihandap Village Bandung with the title "Utilization of waste on melinjo leaves for production of quail egg pindang". The activity aims to give information to the public about the utilization of old melinjo leaf waste for making egg pindang. This activity was attended by housewives and young women as well as Neighborhood Association (RT) administrators (Chairman, Secretary, and Treasurer) of RT 8 RW 06 Jatihandap Village, Mandalajati District, Bandung City. The activity carried out was to introduce the preservation technology of eggs by using old melinjo leaf to produce in the process of making egg pindang. In addition, there were also discussions and demonstrations sessions on the use of pindang eggs for various types of processed foods. This activity received a positive response from the community. The community or participant was also very enthusiastic during the discussion and question-and-answer activities. The participants feel happy because they get the new knowledge and skills about making pindang eggs. With this activity, they know how to use old melinjo leaf waste for making egg pindang. The community also hopes that kind of this community education activity can be held continuously.